(untitled) (III International Congress of Biotechnology and Neotropical Ecosystems, 2026)
Cinchona officinalis is a medicinal plant whose alkaloids are used to treat malaria. In 2020, it was mistakenly believed to be effective against the COVID-19 virus, leading to the collection of individuals from its already scarce relict populations. Since the species produces seeds throughout the year, germination was evaluated according to the month of collection, and subsequently, the rooting of the obtained seedlings was assessed. Seed capsules were collected monthly for 12 months. The seeds were disinfected, soaked, and sown in MS medium. Seedlings were induced to multiply using gibberellins; shoots were isolated, and in a SIT-RITA bioreactor, PBZ and IBA were applied for 1 and 2 minutes every 6 hours to evaluate rooting. Variations in seed size were observed depending on the collection month, as well as differences in germination and rooting. Ex vitro adaptation was improved, considering future conservation and reforestation projects.